Adalimumab effectively reduces the rate of anterior uveitis flares in patients with active ankylosing spondylitis: results of a prospective open-label study. Issue 5 (28th July 2008) - Rudwaleit, M; Rødevand, E; Holck, P; Vanhoof, J; Kron, M; Kary, S; Kupper, H
Abstract : Objective: To evaluate the effect of adalimumab on the frequency of anterior uveitis (AU) flares in patients with active ankylosing spondylitis (AS). Methods: We determined the history of ophthalmologist-diagnosed AU in 1250 patients with active AS who were enrolled in a multinational, open-label, uncontrolled clinical study of treatment with adalimumab, 40 mg every other week for up to 20 weeks. All AU flares were documented throughout the adalimumab treatment period plus 70 days. We compared the rates of AU flares per 100 patient years (PYs) reported during the year before adalimumab treatment with rates during adalimumab treatment, in total and by patient subgroups. Results: The AU flare rates before adalimumab treatment were 15/100 PYs in all patients (n = 1250), 68.4/100 PYs in 274 patients with a history of AU flares, 176.9/100 PYs in 106 patients with a recent history of AU flares, 192.9/100 PYs in 28 patients with symptomatic AU at baseline and 129.1/100 PYs in 43 patients with a history of chronic uveitis. During adalimumab treatment, the rate of AU flares was reduced by 51% in all patients, by 58% in 274 patients with a history of AU, by 68% in 106 patients with a recent history of AU, by 50% in 28 patients with symptomatic AU at baseline and by 45% in 43 patients with chronic uveitis. AU flares during adalimumab treatment were predominantly mild. Two patients with periods of high AS disease activity had new-onset AU during the treatment period. Conclusions: Results of this prospective open-label study suggest that adalimumab had a substantial preventive effect on AU flares in patients with active AS, including patients with a recent history of AU flares. Clinical trials: ClinicalTrials.gov Identifier: NCT00478660.